Security Issue Timing: What Do Managers Know, and When Do They Know It? - JENTER, DIRK; LEWELLEN, KATHARINA; WARNER, JEROLD B. (Journal of Finance, 2011)
ABSTRACT We study put option sales on company stock by large firms. An often‐cited motivation for these transactions is market timing, and managers' decision to issue puts should be sensitive to whether the stock is undervalued. We provide new evidence that large firms successfully time security sales. In the 100 days following put option issues, there is roughly a 5% abnormal stock return, with much of the abnormal return following the first earnings release date after the sale. Direct evidence on put option exercises reinforces these findings: exercise frequencies and payoffs to put holders are abnormally low.